PELATIHAN DAN PENDAMPINGAN OPTIMALISASI KONTEN PRODUK BERBASIS ARTIFICIAL INTELLEGENCE PADA KOMUNITAS UMKM NATAR - Rahsel, Yoeyong; Waziana, Winia; Saputra, Ricco Herdiyan; Pratomo, Panji Andhika; Suprapto, Bambang; Muharni, Sita (Gapenas Publisher, 2024)
UMKM in Indonesia are a top priority in efforts to strengthen the national economy. The Natar UMKM Community, which consists of MSME entrepreneurs in Natar District, is the target of community service activities. Currently, the Natar UMKM Community faces various challenges in managing UMKM digital content where there is a lack of knowledge, understanding and technical skills in utilizing digital technology and AI to create interesting and relevant content for the target market. The aim activities is to increase the understanding and skills of members of the Natar UMKM community in utilizing artificial intelligence (AI) technology to optimize product content. The methods used include socialization, training and mentoring for participants so that they can develop more effective and efficient marketing strategies, and increase the competitiveness of their products in the market. Benefits of the program include increasing the technical capabilities of UMKM members in the use of AI. The results of the activity showed a 52% increase in participants' understanding of the concept of AI and its application in content creation